FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING LOAN DIMODERASI OLEH INFLASI: FACTORS INFLUENCING NON PERFORMING LOAN MODERATED BY INFLATION RATE - Danelia Eka Anisyana; Suherman Suherman; Destria Kurnianti (Yayasan Education and Social Center, 2023)
This study aims to determine the factors influencing non performing loan moderated by inflation rate. Case studies on conventional commercial banks that were listed on the IDX in 2015-2019. This study uses secondary data in the form of financial statements and annual reports. The sampling method used in this study is purposive sampling method. The data analysis technique used in this study is moderated regression analysis. The classical assumption test entails normality, multicollinearity, heteroscedasticity, and autocorrelation tests. While the hypothesis testing entails t-test and coefficient determination test. Data analysis used E-views 12 software. The result showed: LDR and CAR did not significantly influence NPL in a negative direction, NIM had a negative and significant effect on NPL and inflation did not moderate the relationship between LDR, CAR, and NIM on NPL